2014
DOI: 10.4028/www.scientific.net/amr.950.24
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Bacterial Cellulose (BC)/Polyvinil Alcohol (PVA) Nanocomposite as Bone Scaffold

Abstract: This research describes morphological aspect of BC-PVA nanocomposite asscaffold for bone tissue that was synthesized by adding PVA to Gluconacetobacterxylinus fermentation medium. PVA concentrationswere varied as 0,3,6,9, and 12 % (w/v) of the medium. The culture was agitated with magnetic stirrer for 28 days. Freeze drying was then conducted to obtain dry BC/PVA nanocomposite. Some nanocomposite samples subjected to sonication treatments. The morphology of BC-PVA nanocomposite was examined by Scanning Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…39 Accordingly, the vital aim of bone tissue engineering is to provide a desirable scaffold with properties of osteoinductivity and osteoconductivity as well as appropriate porosity for vascularization. 37,40,41 Using BC for the fabrication of biocomposite bone scaffold has attracted the attention of many research groups. The first of these groups was Wan et al 24 who showed that a 3D network of HA-BC nanocomposites had structure similarity to native bone ECM.…”
Section: Application Of Bacterial Cellulose In Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Accordingly, the vital aim of bone tissue engineering is to provide a desirable scaffold with properties of osteoinductivity and osteoconductivity as well as appropriate porosity for vascularization. 37,40,41 Using BC for the fabrication of biocomposite bone scaffold has attracted the attention of many research groups. The first of these groups was Wan et al 24 who showed that a 3D network of HA-BC nanocomposites had structure similarity to native bone ECM.…”
Section: Application Of Bacterial Cellulose In Bone Tissue Engineeringmentioning
confidence: 99%
“…39 Accordingly, the vital aim of bone tissue engineering is to provide a desirable scaffold with properties of osteoinductivity and osteoconductivity as well as appropriate porosity for vascularization. 37,40,41…”
Section: Application Of Bacterial Cellulose In Bone Tissue Engineeringmentioning
confidence: 99%